Information-motivation-behavioral skills barriers associated with intentional versus unintentional ARV non-adherence behavior among HIV+ patients in clinical care. - Norton, Wynne E; Amico, K Rivet; Fisher, William A; Shuper, Paul A; Ferrer, Rebecca A; Cornman, Deborah H; Trayling, Cynthia A; Redding, Caroline; Fisher, Jeffrey D (AIDS care, 2010)
Since the arrival of antiretroviral (ARV) therapy, HIV has become better characterized as a chronic disease rather than a terminal illness, depending in part on one's ability to maintain relatively high levels of adherence. Despite research concerning barriers and facilitators of ARV adherence behavior, relatively little is known about specific challenges faced by HIV-positive persons who report "taking a break" from their ARV medications. The present study employed the Information-Motivation-Behavioral Skills Model of ARV adherence as a framework for understanding adherence-related barriers that may differentiate between non-adherent patients who report "taking a break" versus those who do not report "taking a break" from their ARV medications. A sample of 327 HIV-positive patients who reported less than 100% adherence at study baseline provided data for this research. Participants who reported "taking a break" from their HIV medications without first talking to their healthcare provider were classified as intentionally non-adherent, while those who did not report "taking a break" without first talking with their healthcare provider were classified as unintentionally non-adherent. Analyses examined differences between intentionally versus unintentionally non-adherent patients with respect to demographic characteristics and responses to the adherence-related information, motivation, and behavioral skills questionnaire items. Few differences were observed among the groups on demographics, adherence-related information, or adherence-related motivation; however, significant differences were observed on about half of the adherence-related behavioral skills items. Implications for future research, as well as the design of specific intervention components to reduce intentionally non-adherent behavior, are discussed.
Keywords: Adult; Analysis of Variance; Anti-HIV Agents; Attitude to Health; Female; HIV Infections; HIV Seropositivity; Humans; Male; Medication Adherence; Middle Aged; Models, Theoretical; Motivation; Patient Education as Topic